GÖRÜNTÜ İŞLEME VE YAPAY SİNİR AĞLARI KULLANARAK MİNERAL TANIMA - ABA, FATİH (Fırat Üniveristesi, 2014)
Farklı metot ve algoritmalar kullanılarak mineraller tanımlanabilinir. Bu metotlardan bir tanesi minerallerin mikroskobik (polarize) renklerini kullanarak minerali tanımlamaktır. Renk spektrumunda her bir rengin bir piksel değeri vardır. Bu çalışmada RGB spektrumunda tanımlanan RGB değerleri giriş değerlerini oluşturmak için parametre olarak kullanılmıştır. Çalışmanın birinci safhasında, mineralin ince kesitinden çok sayıda görüntü, mikroskoba monte edilmiş dijital fotoğraf makinesi ile elde edilmiştir. Elde edilen bu görüntüler bilgisayara JPEG formatıyla kaydedilmiştir. Bu görüntülerin piksel değerleri matrise yüklenerek görüntü kümeleri oluşturulmuştur. K-Means algoritması kullanılarak görüntünün piksel değerlerinden elde edilen değerler 3 gruba ayrılmıştır. Çalışmanın ikinci safhasında, birinci safhada elde edilen sonuçlar, oluşturulan yapay sinir ağlarında kullanılarak minerallerin tanımlanması yapılmıştır. Çalışmada kullanılan, alkali feldispat, plajiyoklaz, piroksen ve kuvars mineralleri yaklaşık %12 - %80 doğruluk oranında iken olivin, muskovit, hornbled ve biyotit %64'ün üzerinde doğruluk değeri ile sonuçlanmıştır.

The different methods and algorithms can be used to identify the minerals. One of the methods of identifying minerals is to use the the microscopic / poloarization colors of minerals. Each color has a pixel value in the color spectrum. The pixel values of RGB (Red, Green, Blue) color spectrum are used as parameters to populate the the input data for this study. In the first phase of this study, a lot of images are taken from the thin sections of the minerals by using a digital camera mounted to a microscope. These polorized images are transmitted into the testing and development computer as Joint Photographic Experts Group (JPEG) images. The data which is obtained from the pixel values of one of the images is loaded to the matrixes for further image clustering process. The K-Means algorithm is used to classify the loaded image data based on the pixel values of the mineral. The image data is divided into three clusters using K-Means to avoid the local minima. In the second phase of this study, the output data obtained from the first step is used to train a neural network with forward propagation. Once a neural network with forward propagation training is completed, the neural network identified the minerals. The Alcali Feldspar, Plagioklas, Pyroxene and Quartz Minerals which are used in this study proved with approximately between %12 and %80 accuracy whereas the olivin, muscovite, hornblende, and biotite minerals proved with over than 64% accuracy.
Görüntü işleme ve yapay sinir ağlari kullanarak mineral tanima
Keywords: Jeoloji Mühendisliği